Pelatihan Pembuatan MP-ASI Berbahan Ubi Jalar Kuning dan Ikan Oci kepada Ibu Balita di Posyandu Kumudagu: Training of Making Complementary Food for Breastfeeding with Yellow Sweet Potatoes and Oci Fish to Mother of Children at Posyandu Kumudagu - Sriyanti Sriyanti; Merinta Sada; Mustamir Kamaruddin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The malnutrition among children under five in West Papua was still high, at about 26,2%. This condition was related to nutritional intake that was not optimal. This PkM aims to increase the knowledge of the posyandu cadre and mothers of children in processing local foodstuffs of yellow potato and oci fish into various MP-ASI. This PkM was carried out with two visits targeting cadres and mothers of toddlers. The methods used were counseling about PMBA, demonstration, and training on the manufacture of MP-ASI made from yellow sweet potato and oci fish, testing the level of preference for MP-ASI products, and evaluating knowledge using a questionnaire. The results of the PkM show an increase in the knowledge of kader and mothers of toddlers about PMBA, which is indicated by the level of knowledge of most participants before being given counseling in the less category as much as 62.5% and after being given counseling most of them have a sufficient level of knowledge (68.7%). The level of preference of participants for the biscuit products of yellow sweet potato flour and oci fish meal as a whole showed an average of 4.06, which was included in the liking scale.